Feminine Power and Leadership in Agrarian Affairs : An Analysis of the Ethics of Care in Female Heads of Coffee Farming Families - Fidela Dzatadini Wahyudi (Jurnal Partisipatoris, 2025)
In an agrarian landscape often controlled by masculine norms, the leadership of female heads of coffee farming households presents an alternative paradigm. This study analyzes feminine power and leadership through the lens of the ethic of care, highlighting how care-based leadership challenges gender hierarchies, builds legitimacy through collaborative work, and considers the daily social context of workers. This study uses a phenomenological method with data collection techniques of observation, in-depth interviews, and documentation. The study found that female heads of coffee-farming households are able to lead in ways that differ from the masculine norms prevalent in the agricultural sector. They rely on the ethic of care—prioritizing empathy, closeness, and collaboration to build trust and solidarity within the community. This approach reconstructs power dynamics in the agricultural sphere, opening up more equitable participation opportunities for both women and men.